Berberine Inhibits Nod-Like Receptor Family Pyrin Domain Containing 3 Inflammasome Activation and Pyroptosis in Nonalcoholic Steatohepatitis via the ROS/TXNIP Axis - Mai, Weijian; Xu, Yangzhi; Xu, Jiahui; Zhao, Dan; Ye, Liangying; Yu, Ganxiang; Wang, Zhilei; Lu, Qianting; Lin, Jiaen; Yang, Tao; Gu, Chengxin; Liu, Shiming; et al. (Frontiers in Pharmacology, 2020)
Berberine (BBR), an isoquinoline alkaloid originating from herbal plants, has been deemed beneficial for non-alcoholic fatty liver disease. Increasing evidence has demonstrated that Nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activation and the subsequent pyroptosis contribute to the progression of non-alcoholic steatohepatitis (NASH). However, whether BBR impacts NLRP3 inflammasome activation and pyroptosis in NASH and the potential mechanism remains unclear. In the current study, we found that BBR significantly decreased lipid accumulation, ameliorated reactive oxygen species (ROS) and lipid peroxides, TNF-α expression, and phosphorylation of NF-κB p65 both in vivo and in vitro. In particular, BBR significantly inhibited NLRP3 expression, caspase-1 activity and the pyroptosis executor, GSDMD-N, expression. In addition, BBR displayed similar inhibitory effects on NLRP3 inflammasome and pyroptosis with a decrease in ROS levels and TXNIP expression as N-acetyl-cysteine, a ROS scavenger, did. Whereas, the inhibitory effect of BBR on ROS, TXNIP expression, NLRP3 inflammasome activation and pyroptosis could be reversed by H2O2 in AML12 cells. This study demonstrates that BBR’s inhibitory effect on NLRP3 inflammasome activation and pyroptosis may be mediated by ROS/TXNIP axis in vitro for the first time. Our findings suggest BBR is a potential candidate for the treatment of NASH.